A Solid-State 35Cl and 81Br NMR and Computational Study of Chlorine and Bromine Electric Field Gradient and Chemical Shift Tensors in Haloanilinium Halides - Attrell, Robert J (Université d'Ottawa / University of Ottawa, 2012)
The results of a systematic 35Cl, 81Br, and 127I SSNMR spectroscopic study of a series of halogen-substituted anilinium halide salts are presented. Solid-state NMR of these nuclides, bromine-/81 and iodine-127 in particular, is not well established. Twenty-one compounds thought to exhibit halogen bonding were prepared based on modified literature procedures, and two crystal structures were solved. Experiments show that collection of SSNMR spectra of the anions is feasible, though ultrahigh magnetic fields (21.1 T) and variable offset data acquisition were found to be essential. Electric field gradient and chemical shift tensors are measured experimentally for all 21 compounds, significantly expanding the body of data for the quadrupolar halogen nuclei. Quadrupolar coupling constants for chlorine-35 ranged from 2.12 to 6.04 MHz, for bromine-81 from 12.3 to 45.3 MHz, and for iodine-127 from 57.50 to 152.50 MHz. Gauge-including projector-augmented wave density functional theory (GIPAW-DFT) calculations were used to provide insight as to how the NMR parameters vary with local environment and long-range crystal packing. Overall, calculations reproduced the experimental trends in quadrupolar coupling constants and chemical shift tensor span (Ω) but failed to provide quantitative agreement within experimental error. Experimental and computational data were analyzed in order to provide insight into how halogen bonding influences NMR parameters. Several trends were elucidated from this study, including an inverse correlation between Ω and the length of the shortest halogen-halide contact (d). In selected bromine compounds, for example, Ω (81Br) was measured to increase from 120 to 240 ppm as d decreased from 3.838 to 3.443 Å. In summary, this study has demonstrated the feasibility and utility of quadrupolar halogen SSNMR, and that these techniques may prove useful in characterizing halogen bonding interactions in solids.
Keywords: crystal; shift tensors; Haloanilinium Halides; Halogen bonding; Electric field gradient; magnetic resonance; solid state; quadrupolar halogen SSNMR